The Short Effects of Two Spinal Stabilization Exercise on Balance Tests and Limit of Stability in Men with Non-Specific Chronic Low Back Pain: Randomized Clinical Trial Study - Zahra Ya'ghoubi; Sedigheh Kahrizi; Mohammad Parnian-Pour; Esmaeil Ebrahimi-Takmajani; Soghrat Faghih-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: This study investigated the short-term effects of two stability exercises, including Abdominal Hollowing and Abdominal bracing on stabilization parameters of Biodex Stability System in male subjects with non-specific recurrent low back pain. Materials & Methods: This Randomized Clinical Trial and case-control study was performed on 30 male subjects with non-specific recurrent low back pain by sample of convenience and randomly allocated into 3 control group( 10 subject) and 2 experimental group (10 subject). Dynamic balance stability indices (Overall, Anterior-Posterior and Medial-Lateral) and Limit of Stability were measured by using Biodex Stability System before and immediately after exercise. Results: Our finding showed that all indices except with Medial-Lateral were increased significantly in experimental group in comparison with control. In Abdominal Bracing group, both level of stability of 8 and 3, showed a significant reduction (P<0.05). The limit of Stability in both experimental groups with abdominal Hallowing (P=0.001) and Abdominal Bracing (P=0.01) increased significantly. Conclusion: The findings revealed that one session training enhances balance status, due to muscle activity improvement.